Implikasi current ratio terhadap dinamika pertumbuhan laba: Studi pada sektor konstruksi, properti, dan real estate yang listing di BEI (2022–2023) - Fikri, Muhammad Ilham Ali (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the effect of the current ratio on profit growth in construction, property, and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2023 period. A quantitative approach was used, employing simple linear regression analysis. Data were obtained from annual financial reports and tested using classical assumption tests and statistical analyses (t-test and coefficient of determination). The results show that the current ratio does not have a significant effect on profit growth, indicated by a significance value of 0.064 (greater than 0.05) and an R² value of 0.058. This means that only 5.8% of the variation in profit growth can be explained by the current ratio, while the remaining 94.2% is influenced by other external factors. The findings suggest that liquidity, as measured by the current ratio, is not always a primary driver of profit growth. Other factors such as operational efficiency, business strategy, and market conditions may play a more substantial role in determining a company’s profitability.